O evento 11 de setembro: (re)criação da história no romance Extremely Loud & Incredibly Close (2005), de Jonathan Safran Foer - Vani, João Paulo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This thesis investigates the narrative strategies used by Jonathan Safran Foer in Extremely Loud & Incredibly Close (2005) in order to verify how the author evaluates the episode of the terrorist attacks of 9/11. The tragedy is the beginning of a new period in the history of the United States and has been the subject of publications in several fields. This study examines, through the journey taken by the nine-year-old boy Oskar, whose father was a victim of the 9/11 attacks, how the events of the past are transformed into relevant historical facts, systems that allow the treatment of History through multiple perspectives, and the presence of trauma as a conection between History and Literature. Primarily focusing on the narrator, little Oskar, the analysis will pursue his journey in New York looking for answers to the death of his father on that catastrophic day, treated by Oskar as “the worst day”. The use of images, blanks, written with overlapping and dialogue with technology and coded messages such as SMS, which are present in the novel, will also be analyzed. The theoretical basis of this discussion includes texts by McHale (1992), Lyotard (1990), Jameson (2007), Santiago (2002), Connor (2000), White (1994), Le Goff (2003) and Hutcheon (1991)

Este trabalho investiga as estratégias narrativas utilizadas por Jonathan Safran Foer no romance Extremely Loud & Incredibly Close (2005), a fim de verificar como o autor avalia o episódio dos ataques terroristas de 11 de setembro. A tragédia representa o início de um novo período da História dos Estados Unidos e tem sido tema de publicações em diversas áreas. Este estudo examina, por meio da jornada empreendida pelo menino Oskar, de apenas nove anos, cujo pai foi vítima dos atentados, a forma como os acontecimentos do passado são transformados em fatos históricos relevantes, os sistemas que permitem a abordagem da História por meio de várias perspectivas, e a presença do trauma como elemento de ligação entre História e Literatura. Focalizando primordialmente o narrador, o pequeno Oskar, a análise perseguirá sua jornada em Nova York à procura de respostas para a morte de seu pai naquele dia catastrófico, tratado por Oskar como the worst day. Serão também analisados os usos de imagens, espaços em branco, as escritas com sobreposição e o diálogo com a tecnologia e mensagens codificadas, como SMS, que estão presentes no romance. A fundamentação teórica desta discussão será baseada em textos de McHale (1992), Lyotard (1990), Jameson (2007), Santiago (2002), Connor (2000), White (1994), Le Goff (2003), e Hutcheon (1991)
Keywords: Foer, Jonathan Safran, 1977- Extremely Loud & Incredibly Close Crítica e interpretação; Literatura americana - História e crítica; Ficção histórica americana; Ataques terroristas de 11 de setembro, 2001; Pos-modernismo (Literatura); Cinema e literatura; American literature History and criticism